Food Adulteration: a serious public health concern in Bangladesh (Bangladesh Pharmaceutical Journal, 2015)
Adulteration of foods has become a national issue. The problem is not only ignoring the human rights for safer food but also endangering public health seriously with numerous acute and chronic diseases. Our future generation will be seriously affected with vulnerable physical and mental growth inflicted by food adulteration. This paper describes the impact of consumption of adulterated foods on human health and the roles of the concerned authorities to eradicate it. The key objective of this paper is not to blame or undermine anyone. We intend to inform the current scenario of food adulteration and wish to bring a positive change through proper measures by the concerned regulatory authorities.Bangladesh Pharmaceutical Journal 18(1): 1-7, 2015